Solid electrolyte, laminated body, and fuel cell
By introducing oxygen vacancies and doping elements into the solid electrolyte, adjusting the slope of the lattice volume change, the problem of poor proton diffusion performance in the medium temperature range is solved, and efficient operation of the fuel cell within this temperature range is achieved.
Patent Information
- Application Number
- JP2023149889
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-15
- Publication Date
- 2025-03-28
AI Technical Summary
The poor proton diffusion performance of existing solid electrolytes in the medium temperature range (about 300-400°C), limiting the application of solid fuel cells.
By introducing oxygen vacancies and doping element Mb into the zirconium persulfate structure, the slope of the lattice volume change (∇a/∇b) is adjusted to reduce the energy barrier of protons in the zirconium persulfate, thereby improving the proton diffusion performance.
A solid electrolyte with excellent proton diffusion performance in the medium temperature range is achieved, and the operating performance of the fuel cell in this temperature range is improved.
Smart Images

Figure 2025042768000002 
Figure 2025042768000003 
Figure 2025042768000004
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a solid electrolyte, a laminate, and a fuel cell. [Background technology]
[0002] Depending on the type of electrolyte, there are known types of fuel cells, such as alkaline electrolyte fuel cells, phosphate fuel cells, solid polymer fuel cells, and solid oxide fuel cells. Among them, solid oxide fuel cells are attracting particular attention because they do not use expensive catalysts such as platinum and have high power generation efficiency.
[0003] However, solid oxide fuel cells are not widely used due to the high operating temperature of 700 to 1000°C, the need for preheating to operate them, and the need for durability in the materials that make up the fuel cells. Therefore, in order to lower the operating temperature, studies are being conducted on the use of oxides having a perovskite structure as the proton-conducting oxide electrolyte. For example, Patent Document 1 discloses a solid electrolyte laminate formed from yttrium-added barium zirconate. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2013-206703 A Summary of the Invention [Problem to be solved by the invention]
[0005] The present disclosure has an object to provide a solid electrolyte capable of exhibiting excellent proton diffusion performance in a medium temperature range of about 300 to 400° C. The present disclosure also has an object to provide a laminate including the above-mentioned solid electrolyte. The present disclosure also has an object to provide a fuel cell having excellent operation in a medium temperature range. [Means for solving the problem]
[0006] It is believed that proton diffusion in solid electrolytes occurs by sequential hopping of electron clouds around oxygen atoms in perovskite-type crystals represented by the general formula AMaO3. It is believed that the proton diffusion performance can be controlled by lowering the energy barrier experienced by the protons during this movement. Through investigation, the inventors have found that one method for lowering the energy barrier is to use an AMaO crystal having oxygen vacancies. 3-δ The change in the crystal lattice volume when an additive element (Mb) is dissolved in a perovskite crystal represented by AMaO3 and the change in the crystal lattice volume when Mb is dissolved in a crystal represented by AMaO3, which is filled with oxygen vacancies, are similar to each other. More specifically, the change in the crystal lattice volume when Mb is dissolved in a perovskite crystal represented by AMaO3 is similar to the change in the crystal lattice volume when Mb is dissolved in a crystal represented by AMaO3, which is filled with oxygen vacancies. 3-δ The perovskite crystal represented by AMaO3 (here, AMaO 3-δ A new finding was found that it is important to use a crystal as a host crystal such that the ratio of the change rate (i.e., the slope) of the crystal lattice volume in a graph plotting the relationship between the crystal lattice volume and the addition rate of the element Mb is less than a predetermined value when the vertical axis is the crystal lattice volume of each crystal and the horizontal axis is the addition rate of the element Mb, and the value is less than a predetermined value. Furthermore, it was also found that the change rate of the crystal lattice volume when the amount of Mb added is changed shows a similar tendency regardless of the presence or absence of oxygen vacancies, which corresponds well to the decrease in the activation energy of proton diffusion and the increase in the proton diffusion coefficient. The present disclosure is based on these new findings. The change in the crystal lattice volume is related to the change in the lattice length of the unit lattice in the perovskite crystal, and the fact that the change in the lattice length is small means that the addition of Mb does not cause a large change in the unit lattice and can absorb environmental changes caused by the addition of Mb, and the crystal can be said to have excellent flexibility.
[0007] One aspect of the present disclosure provides the following [1]. [1] General formula: AMaO 3―δ(wherein, in the general formula, A represents an A-site element in the perovskite structure, Ma represents a B-site element in the perovskite structure, and δ is a value less than 3), and an element Mb that substitutes for a part of Ma in the mother crystal to form a solid solution, The mother crystal is AMaO 3―δ The slope of the graph showing the relationship between the change in crystal lattice volume and the substitution solid solution ratio of Mb when Mb is dissolved in a perovskite crystal represented by the formula (1) is ∇a, When the slope of a graph showing the relationship between the change in crystal lattice volume when Mb is dissolved in a crystal represented by AMaO3 in which δ of the perovskite crystal is filled with oxygen atoms and the substitution solid solution ratio of Mb is ∇b, A solid electrolyte that is a crystal with a value of |∇a| / |∇b| that is greater than 0 and less than 1.568.
[0008] When the mother crystal is hard, the value of |∇a| / |∇b| is large, that is, the energy barrier when protons move changes significantly due to the addition of Mb. In contrast, the above solid electrolyte has the above value of |∇a| / |∇b| for the mother crystal within the above-mentioned predetermined range. In a solid electrolyte having such a configuration, the energy barrier when protons move is small in a potential field generated by the overlap of electron clouds around oxygen. This allows the above solid electrolyte to be a solid electrolyte with excellent proton diffusion performance.
[0009] One aspect of the present disclosure provides the following [2] to [9].
[0010] [2] General formula: A(Ma 1-y Mb y )O 3―δ (y is a value greater than 0 and equal to or less than 1, and δ is a value less than 3). [3] The ionic radius of A is r A The weighted average value based on the abundance ratio of the elements of the ionic radii of Ma and Mb is rM Then, (r M / r A ) + C is 0.24 to 0.54, and C is C = 0.55 × r A The solid electrolyte according to [1] or [2], wherein the solid electrolyte has a value of -0.89. [4] The crystal lattice volume is 70.678 × 10 -3 nm 3 More than 85.052 x 10 -3 nm 3 The solid electrolyte according to any one of [1] to [3], which is: [5] Proton conductivity is 1.0×10 -3 Scm -1 The solid electrolyte according to any one of [1] to [4] above. [6] A is at least one selected from the group consisting of Ba, Sr, Ca, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Li, Na, K, Rb, Cs, and Mg; Each of the Ma and Mb is at least one selected from the group consisting of Ti, Zr, Hf, Sn, Pb, Bi, Si, Ge, Ga, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Y, Lu, In, Sc, V, Nb, Ta, Cr, Mo, W, Sb, Mg, Al, As, and Re. The solid electrolyte according to any one of [1] to [5]. [7] General formula:BaSn 1-y Sc y O 3-δ (y is a value of 0.2 to 0.7, and δ is a value of 0.2 to 3), general formula: BaTi 1-y Sc y O 3-δ (y is a value of 0.2 to 0.8, and δ is a value of 0 to 3), or a compound represented by the general formula: BaTi 1-y-x Sn y Sc x O 3-δ(y is a value of 0.05 to 0.15, x is a value of 0.2 to 0.8, and δ is a value of 0 to 3). [8] a first electrode; an electrolyte membrane provided on the first electrode; and a second electrode provided on a side of the electrolyte membrane opposite to the first electrode; 8. A laminate comprising the solid electrolyte according to claim 1, wherein the electrolyte membrane comprises the solid electrolyte according to claim 1. [9] A fuel cell comprising the laminate according to [8]. Effect of the Invention
[0011] According to the present disclosure, it is possible to provide a solid electrolyte capable of exhibiting excellent proton diffusion performance in a medium temperature range of about 300 to 400° C. According to the present disclosure, it is also possible to provide a laminate including the above-mentioned solid electrolyte. According to the present disclosure, it is also possible to provide a fuel cell having excellent operation in a medium temperature range. [Brief description of the drawings]
[0012] [Figure 1] FIG. 1 is a graph showing the relationship between the scandium addition ratio and the crystal lattice volume for various perovskite crystals. [Diagram 2] FIG. 2 is a graph showing the relationship between the proton diffusion coefficient and the activation energy for proton diffusion of the solid oxides prepared in the examples and comparative examples and the proportion of scandium added. [Diagram 3] FIG. 3 is a graph showing the relationship between the proton conductivity of the solid oxides prepared in the examples and comparative examples and the ∇a / ∇b of the host crystals constituting the various solid oxides. [Figure 4] FIG. 4 is a graph showing the results of measuring the proton conductivity of the solid electrolyte prepared in Example 1. [Diagram 5] FIG. 5 is a graph showing the evaluation results of the chemical stability of the solid electrolyte of Example 1. [Figure 6] FIG. 6 is a graph showing the measurement results of the proton diffusion coefficient for the solid electrolyte of Example 1. [Figure 7] FIG. 7 is a diagram showing the results of performance evaluation of the solid electrolyte of Example 1 as an electrolyte for a solar cell. [Figure 8] FIG. 8 is a diagram showing the evaluation results for the solid electrolyte of Example 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] Hereinafter, embodiments of the present disclosure will be described with reference to the drawings in some cases. However, the following embodiments are merely examples for explaining the present disclosure, and are not intended to limit the present disclosure to the following contents. Positional relationships such as up, down, left, and right are based on the positional relationships shown in the drawings unless otherwise specified. The dimensional ratios of each element are not limited to the ratios shown in the drawings.
[0014] Unless otherwise specified, the materials exemplified in this specification may be used alone or in combination of two or more. When a plurality of substances corresponding to each component are present in the composition, the content of each component in the composition means the total amount of the plurality of substances present in the composition, unless otherwise specified. Furthermore, in this specification, a numerical range indicated using "~" indicates a range including the numerical values before and after "~" as the minimum and maximum values, respectively.
[0015] One embodiment of the solid electrolyte has the general formula: AMaO 3―δ and an element Mb which substitutes for a part of Ma in the mother crystal and forms a solid solution. In the above general formula, A represents an A-site element in the perovskite structure, Ma represents a B-site element in the perovskite structure, and δ is a value less than 3. In the above general formula, A, Ma, and Mb are different elements, and O represents oxygen.
[0016] The parent crystal of the solid electrolyte is AMaO 3―δThe crystal may have a value of |∇a| / |∇b| that is greater than 0 and less than 1.568, where ∇a is the slope of a graph showing the relationship between the change in crystal lattice volume when Mb is dissolved in a perovskite crystal represented by the formula (I) and the substitution solid solution ratio of Mb when Mb is dissolved in the perovskite crystal represented by the formula (I), and ∇b is the slope of a graph showing the relationship between the change in crystal lattice volume when Mb is dissolved in a crystal represented by the formula (I) and the substitution solid solution ratio of Mb when Mb is dissolved in the perovskite crystal represented by the formula (I) and the substitution solid solution ratio of Mb when Mb is dissolved in the ... 3 ) and the horizontal axis represents the addition ratio of element Mb.
[0017] The upper limit of the |∇a| / |∇b| value may be, for example, 1.500 or less, 1.300 or less, 1.100 or less, 1.000 or less, or 0.900 or less. When the upper limit of the |∇a| / |∇b| value is within the above range, the energy barrier felt by protons during proton conduction can be further reduced, and the proton diffusion performance of the solid electrolyte can be further improved. The lower limit of the |∇a| / |∇b| value may be, for example, 0.050 or more, 0.100 or more, 0.200 or more, or 0.500 or more. The lower limit of the |∇a| / |∇b| value within the above range corresponds to a more flexible crystal lattice, so that the proton diffusion barrier is further reduced, and the proton diffusion coefficient and proton conductivity are further improved.
[0018] Regarding the above-mentioned ∇a and ∇b, the value of ∇a / ∇b in the host crystal may be, for example, −1 or more and less than 0, or more than 0 and 1 or less, more than 0 and 1 or less, 0.2 to 1.0, or 0.3 to 1.0.
[0019] The composition of the solid electrolyte and the above-mentioned host crystal in this specification can be determined by energy dispersive X-ray analysis (EDS analysis), and the amount of A, Ma, and Mb dissolved is determined by EDS analysis. The unit cell volume of the crystal to be measured is a value obtained by specifying the lattice constants a, b, and c by powder X-ray diffraction at room temperature and multiplying a, b, and c. The pseudocubic volume (hereinafter also referred to as crystal lattice volume) normalized by the number of perovskite units in the unit cell is derived. The crystal lattice volume obtained as described above is plotted against the amount of Mb dissolved in the corresponding crystal, and a straight line graph of linear approximation is created, whereby ∇a and ∇b can be determined. The lattice constants a, b, and c respectively mean the length of the a-axis, the length of the b-axis, and the length of the c-axis of the crystal and the host crystal constituting the solid electrolyte.
[0020] In this specification, when the number of constituent elements of the solid electrolyte is large or the composition formula is unclear, the determination of the above ∇a and the above ∇b is more specifically performed based on the following method. First, the elements constituting the solid electrolyte and the detected concentrations are determined by energy dispersive X-ray analysis (EDS analysis) of the solid electrolyte. Next, among the detected elements, an element having a coordination number of 12 or a lanthanoid element as reported in RD Shannon, “Revised effective ionic radii and systematic studiesod interatomic distance in halides and chalcogenides”, Acta CrystallograhicaSection A, Volume 32, issue 5, 1976 p.751-767, and an element having the highest detected concentration is determined as the element (A1 element) occupying the A site in the mother crystal of the solid electrolyte to be measured. Next, the element (Ma1 element) that is a cationic species with a valence of "6" minus "the valence of the A1 element" and has the highest detected concentration among the elements detected other than the A1 element is taken as the element occupying the B site in the mother crystal of the solid electrolyte to be measured. The element (Mb1 element) that is the highest detected concentration among the elements detected other than the A1 element and the Ma1 element is taken as the element substituting a part of the Ma1 element in the mother crystal of the solid electrolyte to be measured. Using the A1, Ma1, and Mb1 elements thus determined, the mother crystal A1Ma1O 3-δ For A1Ma1O3 and Mb1, the relationship between the crystal lattice volume and the proportion of Mb added is plotted, a linear approximation graph is created, and the slope is determined to determine ∇a and ∇b for the mother crystal of the solid electrolyte to be measured. Note that in the above method, the valences of the elements to be measured are as follows: Ba 2+ , Sr 2+ , Ca 2+ , La 3+ , Ce 4+ ,Pr 3+ , Nd 3+ , Sm3+ , Eu 3+ , Gd 3+ , Tb 3+ , D y3+ , Ho 3+ , Er 3+ , Tm 3+ , Yb 3+ , Lu 3+ , Li 1+ , Na 1+ , K 1+ , Rb 1+ , Cs 1+ , Mg 2+ , Ti 4+ , Zr 4+ , Hf 4+ , Sn 4+ , Pb 4+ , Bi 3+ or Bi 5+ , Si 4+ , Ge 4+ , Ga 3+ , La 3+ , Ce 4+ , Pr 3+ , Nd 3+ , Sm 3+ , Eu 3+ , Gd 3+ , Tb 3+ , Dy 3+ , Ho 3+ , Er 3+ , Tm 3+ , Yb 3+ , Y 3+ , Lu 3+ , In 3+ , Sc 3+ , V 5+ , Nb 5+ , Ta 5+ , Cr 3+ , Mo 5+ or Mo 6+ , W 5+ or W 6+ , Sb 3+ or Sb 5+ , Mg 2+ , Al 3+ , As 5+ , Re 6+
[0021] The mother crystal and the solid electrolyte have a perovskite-type crystal structure. It can be confirmed by X-ray diffraction that the mother crystal and the solid electrolyte have a perovskite-type crystal structure.
[0022] The solid electrolyte has the general formula: A(Ma 1-y Mb y )O 3―δ (y is a value greater than 0 and equal to or less than 1, and δ is a value less than 3), 1-y Mb y )O 3―δ (wherein y is a value of 0.3 or more and 1 or less, and δ is a value of less than 3), 1-y Mb y )O 3―δ (y is a value of 0.5 or more and 1 or less, and δ is a value less than 3). Since protons are introduced into the above solid electrolyte during use, the above solid electrolyte may be represented by the general formula: A(Ma 1-y Mb y )O 3―δ H z (y is a value of 0.5 or more and 1 or less, δ is a value less than 3, and z is a value that varies depending on the proton to be introduced).
[0023] The above A includes, for example, at least one selected from the group consisting of Ba, Sr, Ca, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Li, Na, K, Rb, Cs, and Mg, and from the viewpoint of making the crystal lattice volume more appropriate, it may be at least one selected from the group consisting of Cs, Rb, K, Na, Ba, Sr, La, Pr, and Nd, and from the viewpoint of further improving the chemical stability of the obtained solid oxide, it may be at least one selected from the group consisting of Ba, Sr, La, Pr, and Nd.
[0024] The Ma includes at least one selected from the group consisting of, for example, Ti, Zr, Hf, Sn, Pb, Bi, Si, Ge, Ga, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Y, Lu, In, Sc, V, Nb, Ta, Cr, Mo, W, Sb, Mg, Al, As, and Re. From the viewpoint of making the crystal lattice volume more appropriate, the Ma includes at least one selected from the group consisting of Sn, Ti, Zr, Hf, Pb, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Y, Lu, In, Sc, V, Nb, Ta, Cr, Mo, W, Sb, Mg, Al, As, and Re. From the viewpoint of further improving the chemical stability of the obtained solid oxide, it may be at least one selected from the group consisting of Ti, Zr, Hf, Sn, Si, Ge, Ga, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Y, Lu, In, Sc, V, Nb, Ta, Cr, Sb, Mg, Al, and Re.
[0025] The Mb includes at least one selected from the group consisting of, for example, Ti, Zr, Hf, Sn, Pb, Bi, Si, Ge, Ga, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Y, Lu, In, Sc, V, Nb, Ta, Cr, Mo, W, Sb, Mg, Al, As, and Re. From the viewpoint of making the crystal lattice volume more appropriate, the Mb includes at least one selected from the group consisting of Sn, Ti, Zr, Hf, Pb, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Y, Lu, In, Sc, V, Nb, Ta, Cr, Mo, W, Mg, and R. From the viewpoint of further improving the chemical stability of the obtained solid oxide, it may be at least one selected from the group consisting of Ti, Zr, Hf, Sn, Si, Ge, Ga, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Y, Lu, In, Sc, V, Nb, Ta, Cr, Sb, Mg, Al, and Re, and from the viewpoint of increasing the bulk modulus and further improving the flexibility of the crystal lattice, it may be at least one selected from the group consisting of Sc, Ti, Sn, Pb, and In.
[0026] The A, Ma, and Mb may each contain a plurality of elements so long as they are different from one another.
[0027] More specifically, the solid electrolyte is, for example, represented by the general formula: BaSn 1-y Sc y O 3-δ (y is a value of 0.2 to 0.7, and δ is a value of 0.2 to 3), 1-y Sc y O 3-δ (y is a value of 0.2 to 0.8, and δ is a value of 0 to 3), or a compound represented by the general formula: BaTi 1-y-x Sn y Sc x O 3-δ (y is a value of 0.05 to 0.15, x is a value of 0.2 to 0.8, and δ is a value of 0 to 3).
[0028] The composition of the solid electrolyte and the matrix crystal in this specification can be determined by energy dispersive X-ray analysis (EDS analysis). The surface of the dense body of the solid electrolyte sintered in dry air is polished to 100 μm or more with silicon carbide abrasive paper to be measured. The surface of the sample is irradiated with an electron beam accelerated at 15 kV, and the characteristic X-ray intensity generated by this is observed using a scanning electron microscope (SEM), thereby determining the composition of the solid electrolyte and the matrix crystal. The ZAF method is used as the quantitative method. As the scanning electron microscope, for example, "SU3500" (product name) manufactured by Hitachi High-Tech Technologies Co., Ltd., "AZtecEnergy" (product name) manufactured by Oxford Instruments, etc. can be used.
[0029] In the above solid electrolyte, the ionic radius of A is r A The weighted average value based on the abundance ratio of the elements of the ionic radii of Ma and Mb is r M Then, (r M / r A The value of C = 0.55 × rA It is expressed as -0.89. (r M / r A When the value of (r)+C is within the above range, the crystal lattice becomes softer, the proton diffusion barrier is lowered, and the proton diffusion coefficient and the proton conductivity are improved. M / r A The lower limit of the value of (r)+C may be, for example, 0.260 or more, 0.300 or more, 0.400 or more, 0.430 or more, 0.437 or more, 0.440 or more, or 0.443 or more. M / r A When the lower limit of the value of (r)+C is within the above range, the crystal lattice becomes softer, the proton diffusion barrier is further lowered, and the proton diffusion coefficient and the proton conductivity are further improved. M / r A The upper limit of the value of (r)+C may be, for example, 0.500 or less, 0.480 or less, 0.460 or less, 0.458 or less, or 0.456 or less. M / r A When the lower limit of the value of )+C is within the above range, the crystal lattice becomes softer, which further reduces the proton diffusion barrier, and the proton diffusion coefficient and the proton conductivity are each further improved.
[0030] The lower limit of the crystal lattice volume of the solid electrolyte is, for example, 70.678 × 10 ―3 nm 3 That's it, 71.965 x 10 ―3 nm 3 That's it, 72.490 x 10 ―3 nm 3 or more, or 73.000 x 10 ―3 nm 3 When the lower limit of the crystal lattice volume is within the above range, the crystal lattice becomes softer, the proton diffusion barrier is further lowered, and the proton diffusion coefficient and the proton conductivity are further improved. The upper limit of the crystal lattice volume of the solid electrolyte is, for example, 85.052×10 ―3 nm 3 The following is 83.000 x 10 ―3 nm 3 Below, 80.000 x 10 ―3 nm3 The following is 78.000 x 10 ―3 nm 3 Below, 75.000 x 10 ―3 nm 3 The following is 73.665 x 10 ―3 nm 3 or 72.417 x 10 ―3 nm 3 When the upper limit of the crystal lattice volume is within the above range, the crystal lattice becomes softer, the proton diffusion barrier is further lowered, and the proton diffusion coefficient and the proton conductivity are further improved. The crystal lattice volume of the solid electrolyte may be adjusted within the above range, for example, 70.678×10 -3 nm 3 More than 85.052 x 10 -3 nm 3 or less, or 70.678 x 10 -3 nm 3 More than 72.417 x 10 -3 nm 3 The following may be true:
[0031] The above-mentioned solid electrolyte has excellent proton diffusion performance in the medium temperature range of about 300 to 400° C. The lower limit of the proton conductivity of the above-mentioned solid electrolyte at 300 to 400° C. is, for example, 1.0×10 -3 Scm -1 That's it, 2.0 x 10 -3 Scm -1 That's it, 3.0 x 10 -3 Scm -1 or more, or 10 x 10 -3 Scm -1 The upper limit of the proton conductivity of the solid electrolyte at 300 to 400° C. is not particularly limited, but is usually 30×10 -3 Scm -1 or less, or 20 x 10 -3 Scm -1 The following is the result.
[0032] The proton conductivity in the intermediate temperature range in this specification can be determined by AC impedance measurement. Specifically, it is determined according to the method described in the Examples of this specification. Note that the above proton conductivity is the proton conductivity in the crystal grains, i.e., the proton conductivity in the bulk (σ H.bulk ) and is expressed as the minimum value in the temperature range of 300 to 400°C.
[0033] The solid electrolytes described above can be prepared by solid-phase synthesis or solution synthesis.
[0034] An example of a method for producing a solid electrolyte includes a step of pulverizing a raw material mixture containing a compound having A as a constituent element, a compound having Ma as a constituent element, and a compound having Mb as a constituent element to obtain a powder (pulverizing step), a step of pressure-molding the pulverized product to obtain a molded product (molding step), and a step of heat-treating the molded product at a temperature of 800 to 1700°C to obtain a sintered body (sintering step). The A, Ma, and Mb each represent a different element, and the explanation of A, Ma, and Mb described in the above solid electrolyte can be applied. The pressure molding may include, for example, uniaxial pressure molding and cold isotropic compression.
[0035] The compound having A as a constituent element, the compound having Ma as a constituent element, and the compound having Mb as a constituent element may be oxide, nitrate, or carbonate, independently of each other. Examples of the compound having A as a constituent element include barium carbonate and barium nitrate. Examples of the compound having Ma as a constituent element include tin oxide and titanium oxide. Examples of the compound having Mb as a constituent element include scandium oxide and scandium nitrate.
[0036] The sintering step may be carried out, for example, in the atmosphere. The heating temperature in the sintering step may be, for example, 1200 to 1700° C., 1400 to 1700° C., or 1600 to 1700° C. The temperature rise rate in the sintering step may be, for example, 100 to 250° C. / hour, 150 to 230° C. / hour, or 180 to 200° C. / hour.
[0037] The above-mentioned solid electrolyte is useful as a component of, for example, a fuel cell. Specific examples of the component include a laminate in which the above-mentioned solid electrolyte is disposed between electrodes. One embodiment of the laminate includes a first electrode, an electrolyte membrane provided on the first electrode, and a second electrode provided on the electrolyte membrane on the side opposite to the first electrode. The electrolyte membrane includes the above-mentioned solid electrolyte.
[0038] The first electrode and the second electrode may be made of the same material or different materials. When the laminate is a component of a fuel cell, for example, the first electrode may be an anode electrode (fuel electrode) and the second electrode may be a cathode electrode (air electrode).
[0039] The material of the anode electrode may be, for example, silver, platinum, palladium, nickel, a mixture of nickel and zirconia-based oxide, nickel and ceria-based oxide, and a mixture of nickel and barium zirconate-based oxide.
[0040] The material of the cathode electrode can be, for example, a perovskite-type oxide containing silver, platinum, a rare earth element, and a 3d transition metal. Such a perovskite-type oxide can be, for example, a perovskite-type oxide represented by the general formula: D1 1-a D2 a B1 1-b B2 b Oxides represented by the formula O3 (0≦a≦1, 0≦b≦1) can be used. Here, D1 and D2 may be lanthanides (Ln) such as lanthanum (La), cerium (Ce), praseodymium (Pr), and samarium (Sm), or alkaline earth metals (AE) such as calcium (Ca), strontium (Sr), and barium (Ba). B1 and B2 may be manganese (Mn), iron (Fe), and cobalt (Co). Specific examples of the material of the cathode electrode include Ln 1-a AE a Mn 1-b Fe b O3, Ln 1-a AE aMn 1-b Co b O3 and Ln 1-a AE a Co 1-b Fe b O3, A.E. 1-a AE a Co 1-b Fe b It may be O3 etc.
[0041] The thickness of the first electrode and the second electrode can be adjusted depending on the application of the laminate, etc.
[0042] The thickness of the electrolyte membrane can be adjusted according to the performance required for the laminate and the use of the laminate. The upper limit of the thickness of the electrolyte membrane may be, for example, 500 μm or less, 400 μm or less, 300 μm or less, 150 μm or less, 50 μm or less, 25 μm or less, or 15 μm or less. By setting the upper limit of the thickness of the electrolyte membrane within the above range, the proton conductivity can be further improved. The lower limit of the thickness of the electrolyte membrane may be, for example, 0.1 μm or more, 0.5 μm or more, 1.0 μm or more, 3 μm or more, 5 μm or more, or 10 μm or more. By setting the lower limit of the thickness of the electrolyte membrane within the above range, the decrease in the mechanical strength of the electrolyte membrane itself can be suppressed and the dielectric breakdown between the electrodes can be more sufficiently suppressed. The thickness of the electrolyte membrane can be adjusted within the above range and may be, for example, 0.1 to 500 μm, 0.1 to 400 μm, 1.0 to 400 μm, 1.0 to 50 μm, or 5 to 15 μm.
[0043] The laminate may include other layers in addition to the first electrode, the electrolyte membrane, and the second electrode. Examples of the other layers include a layer inserted between the first electrode and the electrolyte, and a layer inserted between the second electrode and the electrolyte. Examples of the layer inserted between the first electrode and the electrolyte include a nickel and barium zirconate-based mixture layer, a nickel and zirconia-based oxide mixture layer, and a nickel and cerium oxide-based oxide mixture layer. Examples of the layer inserted between the second electrode and the electrolyte include a cerium oxide-based oxide, a barium zirconate-based oxide, a cerium-added barium zirconate-based oxide, and a barium cerate-based oxide.
[0044] The solid oxide fuel cell having the laminate contains the above-mentioned solid oxide as an electrolyte, so that the operating temperature can be set low. The upper limit of the operating temperature of the solid oxide fuel cell can be, for example, 600°C or less, 550°C or less, 500°C or less, 450°C or less, 350°C or less, or 250°C or less. The lower limit of the operating temperature of the solid oxide fuel cell can be, for example, 100°C or more, 200°C or more, or 300°C or more. The operating temperature of the solid oxide fuel cell can be adjusted within the above-mentioned range, and may be, for example, 250 to 600°C or 100 to 590°C. The solid oxide fuel cell having the laminate also contains the above-mentioned solid oxide as an electrolyte, so that it can be stably operated for a long period of time (for example, 200 hours or more).
[0045] Although several embodiments have been described above, the present disclosure is not limited to the above-described embodiments. In addition, the contents of the descriptions of the above-described embodiments can be mutually applied. EXAMPLES
[0046] The present disclosure will be described in more detail below with reference to examples and comparative examples. However, the present disclosure is not limited to the following examples.
[0047] [Selection of host crystal candidates] Barium stannate (BaSnO3), barium titanate (BaTiO3), and barium zirconate (BaZrO3) were prepared, and the unit cell volume and the number of perovskite units in the unit cell were determined by powder X-ray diffraction when a portion of the B-site atoms in the perovskite structure, i.e., Sn, Ti, and Zr, were replaced with scandium (Sc). The crystal lattice volume was determined for each addition ratio while changing the addition ratio of scandium. Next, barium stannate (BaSnO 3―δ ), barium titanate (BaTiO 3―δ ), and barium zirconate (BaZrO 3―δ ) was prepared and similar measurements were performed. The results are shown in Figure 1. Table 1 also shows the values of ∇a and ∇b, which are the rates of change in the crystal lattice volume corresponding to each graph.
[0048] [Table 1]
[0049] Example 1 [Ba(Sn 0.3 Sc 0.7 )O 3―δ Preparation of scandium-doped barium stannate represented by the formula: Barium carbonate (BaCO3, Fujifilm Wako Pure Chemicals, purity: 99.9% by mass), tin oxide (SnO2, HIGH PURITY CHEMICALS, purity: 99.9% by mass), and scandium oxide (Sc2O3, HIGH PURITY CHEMICALS, purity: 99.9% by mass or more) were weighed out in a container so as to have a stoichiometric ratio according to the composition formula of the target scandium-added barium stannate (composition formula in which y is 0.7 in the general formula), and were placed in a mortar together with a specified amount of ethanol and wet mixed. The mixture was heated to 1100°C at a heating rate of 300°C / hour in the atmosphere, and heat-treated at the temperature of 1100°C for 5 hours to obtain a calcined powder.
[0050] The calcined powder was placed in a container, a predetermined amount of ethanol and zirconia balls were added, and the mixture was wet-milled at a rotation speed of 300 rpm for 3 days using a roller mill (NITTO KAGAKU CO. LTD. ANZ-52D) to obtain a pulverized material. The pulverized material was dried to obtain the raw material powder.
[0051] The obtained raw material powder was molded into pellets with a diameter of 20 mm and a thickness of about 2 mm using a uniaxial pressing machine, and further pressed at 250 MPa by cold isostatic pressing. The pellets were heated to 1600°C while flowing dry air at a flow rate of 100 mL / min, and heat-treated at a temperature of 1600°C for 12 hours to obtain a sintered body. The heat treatment of the above-mentioned pellets was performed in a state where the pellets were covered with a powder having the same composition as the above-mentioned raw material powder in order to prevent the barium component from leaking out of the system and disturbing the composition. The diameter was shrunk to 13.5 mm by sintering, and the density of the sintered body was 5.6 g / cm. 3 The composition of the sintered body was analyzed by X-ray diffraction (XRD) and confirmed to have a single perovskite structure. The composition of the sintered body was also analyzed by energy dispersive X-ray spectroscopy (EDS) and confirmed to be Ba(Sn 0.3 Sc 0.7 )O 3―δ It was confirmed that the cationic composition was:
[0052] Example 2 [Ba(Ti 0.2 Sc 0.8 )O 3―δ Preparation of scandium-doped barium titanate represented by the formula A calcined powder was obtained in the same manner as in Example 1, except that titanium oxide (TiO2, manufactured by HIGH PURITY CHEMICALS, purity: 99.99 mass%) was used instead of tin oxide in Example 1, and was measured so as to have a stoichiometric ratio according to the composition formula of the target scandium-added barium titanate (composition formula in which y is 0.8 in the general formula). Thereafter, the calcined powder obtained was placed in a container, a predetermined amount of ethanol and zirconia balls were added, and the powder was wet-pulverized at a rotation speed of 300 rpm for 1 hour using a planetary ball mill (manufactured by Fritsch, product name: planetary ball mill Pulverisette 7) to obtain a pulverized product. The pulverized product was dried to obtain a raw material powder. The obtained raw material powder was formed into a pellet shape with a diameter of 20 mm and a thickness of about 2 mm using a uniaxial pressing molding machine, and further pressed at 250 MPa by a cold isostatic pressing method. The pellets were heated to 1600°C while passing dry air at a flow rate of 100 mL / min, and heat-treated at 1600°C for 24 hours to obtain a sintered body. The heat treatment of the pellets was performed in a state where the pellets were covered with the powder, as in Example 1. The diameter of the pellets was shrunk to 14.2 mm by sintering, and the density of the sintered body was 5.0 g / cm. 3 The composition of the sintered body was analyzed by X-ray diffraction (XRD) and confirmed to have a single perovskite structure. The composition of the sintered body was also analyzed by energy dispersive X-ray spectroscopy (EDS) and confirmed to be Ba(Ti 0.2 Sc 0.8 )O 3―δ It was confirmed that the cationic composition was:
[0053] Example 3 [Ba(Sn 0.15 Ti 0.05 Sc 0.8 )O 3―δ Preparation of scandium-doped barium tin titanate represented by the formula: A calcined powder was obtained in the same manner as in Example 1, except that barium carbonate (BaCO3, manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd., purity: 99.9% by mass), tin oxide (SnO2, manufactured by HIGH PURITY CHEMICALS, Inc., purity: 99.9% by mass), titanium oxide (TiO2, manufactured by HIGH PURITY CHEMICALS, Inc., purity: 99.99% by mass), and scandium oxide (Sc2O3, manufactured by HIGH PURITY CHEMICALS, Inc., purity: 99.9% by mass or more) were weighed out and placed in a container in a stoichiometric ratio according to the composition formula of the desired scandium-doped barium tin titanate (composition formula in which y is 0.8 in the general formula). The calcined powder was then placed in a container, a predetermined amount of ethanol and zirconia balls were added, and the mixture was wet-pulverized for 3 hours at a rotation speed of 300 rpm using a planetary ball mill (manufactured by Fritsch, product name: planetary ball mill Pulverisette 7) to obtain a pulverized product. The pulverized product was then placed in a container, a predetermined amount of ethanol and zirconia balls were added, and the mixture was wet-pulverized for 3 days at a rotation speed of 300 rpm using a roller mill (NITTO KAGAKU CO.LTD.ANZ-52D) to obtain a pulverized product. The pulverized product was dried to obtain a raw material powder. The raw material powder obtained was molded into a pellet shape with a diameter of 15 mm and a thickness of about 2 mm using a uniaxial pressing machine, and further pressed at 300 MPa by a cold isostatic pressing method. The pellet was heated to 1600°C while flowing dry air at a flow rate of 100 mL / min, and heat-treated at a temperature of 1600°C for 12 hours to obtain a sintered body. The pellets were heat-treated in the same manner as in Example 1, with the pellets covered with the powder. The composition of the resulting sintered body was analyzed by X-ray diffraction (XRD) and confirmed to have a single perovskite structure. The composition of the resulting sintered body was also analyzed by energy dispersive X-ray spectroscopy (EDS) and confirmed to be Ba(Sn 0.15 Ti 0.05 Sc 0.8 )O 3―δ It was confirmed that the cationic composition was:
[0054] Comparative Example 1 [Ba(Zr 0.4 Sc 0.6) O3-δ Preparation of scandium-doped barium zirconate represented by the formula: Barium nitrate (Fujifilm Wako Pure Chemical Industries, Ltd., Ba(NO3)2, purity: 99.9% by mass), zirconium oxynitrate dihydrate (Kanto Chemical Co., Ltd., ZrO(NO3)2·2H2O), and scandium nitrate n-hydrate (Kojundo Chemical Laboratory Co., Ltd., Sc(NO3)3·nH2O, purity: 3N) were weighed out in a container so as to have a stoichiometric ratio according to the composition formula of the target scandium-doped barium zirconate (composition formula in which x is 0.6 in the general formula), and dissolved in approximately 800 mL of distilled water to prepare an aqueous solution. Note that the amount of hydrate was adjusted after confirming the amount of hydration by thermogravimetric analysis.
[0055] To the above aqueous solution, ethylenediaminetetraacetic acid (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd., EDTA, purity: 99.0% by mass) and citric acid (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd., purity: 99.0% by mass) were further added so that each was 0.5 molar based on the total molar number of metal ions in the aqueous solution, and the pH of the reaction solution was adjusted to 9.0 to 10 with an aqueous ammonia solution to dissolve the added reagents and obtain a reaction solution. Next, the reaction solution was heated for about 300 minutes while stirring on a hot stirrer, and the contents were reacted and the solvent was removed from the system. At this time, the surface temperature of the hot stirrer was adjusted to 180° C. The obtained gel-like material was heated in a microwave heating furnace to remove the solvent contained in the gel-like material and obtain a solid material.
[0056] The solid obtained as described above was placed in a heating furnace, heated from room temperature at a temperature increase rate of 5°C / min, and fired for 10 hours after reaching 900°C to obtain a precursor. The obtained precursor was placed in a container, a predetermined amount of ethanol and zirconia balls were added, and wet-pulverized for 2 hours at a rotation speed of 300 rpm using a planetary ball mill (manufactured by Fritsch, product name: planetary ball mill Pulverisette 7) to obtain a pulverized product. The pulverized product was dried. At the end of this pulverization process, it was confirmed by X-ray diffraction that the product was a mixture of scandium-added barium zirconate, scandium-added zirconium oxide, and barium carbonate.
[0057] The ground mixture was molded into pellets with a diameter of 20 mm and a thickness of approximately 2 mm using a uniaxial pressing machine, and further pressed at 300 MPa using a cold isostatic pressing method. The pellets were heat-treated at 1600°C for 24 hours while flowing dry air at a flow rate of 100 mL / min to obtain a sintered body. The diameter of the sintered body was shrunk to 15 mm, and the density of the sintered body was 5.3 g / cm. 3 The composition of the sintered body was analyzed by X-ray diffraction (XRD) and confirmed to have a single perovskite structure. The composition of the sintered body was also analyzed by energy dispersive X-ray spectroscopy (EDS) and confirmed to be BaZr 0.4 Sc 0.6 O 3―δ It was confirmed that the cationic composition was:
[0058] [Proton conductivity of solid electrolyte (σ H。bulk )measurement] For the solid electrolytes prepared in Examples 1 and 2 and Comparative Example 1, the proton conductivity (σ H。bulk ) was measured by AC impedance measurement.
[0059] Specifically, first, both sides of the sintered body were polished to a thickness of about 500 μm. Next, a silver layer having a thickness of 650 nm was formed on each side of the polished sintered body using a DC sputtering device (manufactured by Sanyu Electronics Co., Ltd., product name: SC-701HMC II), and this was used as a measurement sample.
[0060] A current collector consisting of a silver mesh (manufactured by Nilaco Corporation) and a gold wire with a diameter of 0.1 mm was prepared, and a silver paste (manufactured by Tanaka Kikinzoku Kogyo Co., Ltd., product name: TR-3025) was applied to the current collector. The current collector was attached to both polished surfaces of the measurement sample, and the paste was dried in a dryer at a temperature of 55°C. The obtained laminate was heat-treated in a dry argon atmosphere at about 800°C for 1 hour to obtain a measurement sample. The measurement sample was connected to an electrochemical measurement cell with an atmosphere controllable via a gold wire. The measurement sample was heated to about 720°C in a dry argon atmosphere, and at the same time that the temperature reached 720°C, the atmosphere was switched to an argon atmosphere with a water vapor pressure of 0.02 atm. Thereafter, the temperature was lowered and the impedance was measured by an AC impedance method in a temperature range of about 600 to 30°C, with a capacitance of 0.1 to 10. 6 The proton conductivity was measured by sweeping the frequency from 100 to 150 Hz. The measurements at each temperature were performed by continuously measuring the AC impedance, and were continued until the resistance value was stabilized to a level where it no longer changed. From the measurement results, the proton conductivity in the bulk (σ H。bulk ) was determined. The relationship between ∇a / ∇b and the proton conductivity of each host crystal is shown in FIG. 3. For reference, the temperature dependence of the proton conductivity measured for the solid electrolyte of Example 1 is shown in FIG.
[0061] [Measurement of proton concentration] The proton concentration of the solid electrolytes prepared in Examples 1 to 3 and Comparative Example 1 was measured by thermogravimetric analysis. Specifically, the sintered body used in the measurement of proton conductivity was pulverized in an agate mortar to obtain a pulverized material. The obtained powder was subjected to a heat treatment at 1000°C for 1 hour in a dry argon atmosphere using a thermogravimetric analyzer (manufactured by Netsch, product name: STA449F3 Jupiter). The atmosphere surrounding the pulverized material was humidified with water vapor to measure the water vapor partial pressure (p H2O) to 0.02 atm, protons were introduced into each solid oxide. The atmosphere was switched to a humidified state, and the temperature was maintained until no mass change occurred and equilibrium was reached. Assuming that the oxygen vacancies in each solid oxide were hydrated by water molecules, the proton introduction rate was calculated from the mass increase observed in the above operation.
[0062] Next, the temperature of the sintered body was gradually lowered to about 115°C to obtain the temperature dependence of the proton introduction rate. By gradually lowering the temperature, the proton introduction rate increased, and the proton introduction rate for each solid oxide at about 300°C, that is, the proton introduction rate for the general formula: AMa 1-y Mb y O 3-δ H z For example, for the solid oxide of Example 3, the value of z was determined as follows: Ba(Sn 0.15 Ti 0.05 Sc 0.8 )O 3―δ H z The z in was determined to be 0.70. For reference, the results for the solid oxides of Examples 2 and 3 are shown in FIG.
[0063] [Measurement of proton diffusion coefficient and activation energy for proton diffusion in solid electrolytes] The solid electrolytes prepared in Examples 1 to 3 and Comparative Example 1 were subjected to measurement of the proton diffusion coefficient and the activation energy for proton diffusion. Specifically, the proton diffusion coefficient can be determined by dividing the proton concentration from the obtained proton conductivity according to the Nernst-Einstein equation. According to the definition of the Arrhenius plot, the activation energy for proton diffusion was determined from the slope of the proton diffusion coefficient plotted against the reciprocal of temperature. The results for the solid oxides of Examples 1 and 2 and Comparative Example 1 are shown in FIG. 2. FIG. 2(a) is a graph showing the measurement results of the proton diffusion coefficient, and FIG. 2(b) is a graph showing the measurement results of the activation energy for proton diffusion.
[0064] [Evaluation of chemical stability of solid electrolytes] The solid electrolyte prepared in Example 1 was evaluated for chemical stability. Specifically, the proton conductivity was measured continuously for 258 hours while the water vapor supplied to the measurement sample was replaced between heavy water (D2O) and light water (H2O). The measurement conditions were water vapor pressure: 0.02 atm, and temperature: 301°C. Note that the proton conductivity when heavy water was supplied was 5.61×10 -3 Scm -1 When light water was supplied, the proton conductivity was 10.60×10 -3 Scm -1 The results are shown in Figure 5.
[0065] As shown in FIG. 5, the solid electrolyte prepared in Example 1 maintained its proton conductivity for at least 258 hours, and it was confirmed that the obtained solid electrolyte had excellent chemical stability.
[0066] [Proton diffusion coefficient in bulk of solid electrolyte (D H。bulk ) Evaluation For the solid electrolyte prepared in Example 1, the proton diffusion coefficient in scandium-doped barium stannate was evaluated by measuring by an AC impedance method.
[0067] Specifically, D H。bulk =(σ H。bulk RT) / (F 2 C H ) where R is the gas constant, T is the temperature, F is the Faraday constant, and C H is the proton concentration. The proton diffusion coefficient was calculated by substituting the proton conductivity and proton concentration at each temperature. The Arrhenius plot of the obtained proton diffusion coefficient is shown in Figure 6. For comparison, Figure 6 also shows the results for scandium-doped barium zirconate and yttrium-doped barium zirconate.
[0068] [Evaluation as a solid electrolyte for fuel cells] The solid electrolyte prepared in Example 1 was evaluated as a solid electrolyte for a fuel cell.
[0069] Specifically, first, both sides of the pellet-shaped sintered body (solid electrolyte) with a diameter of 15 mm prepared in Example 1 were polished so that the thickness of the pellet was 0.3 mm (300 μm). After polishing, platinum paste (manufactured by Tanaka Kikinzoku Kogyo Co., Ltd., product name: TR-7907) was applied to both polished surfaces of the pellet to form a circle with a diameter of 8 mm, and the mixture was fired at 700°C for 2 hours in a dry air atmosphere, and then the temperature was lowered to 100°C for 100 hours in a humid atmosphere with a relative humidity of 2% RH to form a platinum electrode. In addition, a platinum mesh was placed on the platinum electrode formed as described above so as to be in contact with it, and silver paste (manufactured by Tanaka Kikinzoku Kogyo Co., Ltd., product name: TR-3205) was applied. After drying the silver paste, 60 μL of 2 mol% cerium nitrate was dropped on both electrodes, and the mixture was fired at 300°C for 2 hours in a humid atmosphere with a relative humidity of 2% RH. After firing, the electrode surface turned black due to the influence of cerium nitrate. One electrode corresponds to the anode and the other to the cathode. Next, a platinum wire was wrapped around the side of the pellet to serve as a reference electrode. In this way, the evaluation sample was prepared.
[0070] As shown in FIG. 7(a), a circuit incorporating an evaluation sample was prepared. Then, the relationship between the cell voltage and the power density and the current density was measured. In addition, the transition of the proton conductivity when the device was operated continuously for 100 hours was confirmed. The results are shown in FIG. 7. FIG. 7(b) is a graph showing the relationship between the cell voltage and the power density and the current density. FIG. 7(c) is a graph showing the time dependency of the proton conductivity under the fuel cell operating conditions. From the results, it was confirmed that the solid electrolyte prepared in Example 1 can exert a theoretical open circuit electromotive force corresponding to the gas atmosphere on the cathode side and the anode side. It was also confirmed that the fuel cell can be operated stably for 100 hours.
[0071] [Ba(Sn 0.15 Ti 0.05 Sc 0.8 )O 3―δ The proton diffusion coefficient (D) in the bulk of scandium-doped barium tin titanate is H。bulk) and proton conductivity (σ H。bulk ) Measurement For the solid oxide prepared in Example 3, the proton diffusion coefficient in bulk (D H。bulk ) and proton conductivity (σ H。bulk The measurement conditions were the same as those for the solid oxide in Example 1. The results are shown in (b) and (c) of FIG. 8. (b) and (c) of FIG. 8 show the Ba(Ti 0.2 Sc 0.8 )O 3―δ As shown in FIG. 8(c), the measurement results for scandium-doped barium titanate, represented by Ba(Sn 0.15 Ti 0.05 Sc 0.8 )O 3―δ Scandium-doped barium tin titanate, expressed as -3 Scm -1 It was confirmed that the results exceeded the standards and were excellent. [Industrial Applicability]
[0072] According to the present disclosure, it is possible to provide a solid electrolyte capable of exhibiting excellent proton diffusion performance in the mid-temperature range of about 300 to 400° C. According to the present disclosure, it is also possible to provide a fuel cell that is excellent in operation in the mid-temperature range.
Claims
1. General formula: AMaO 3―δ (in the general formula, A represents an A-site element in the perovskite structure, Ma represents a B-site element in the perovskite structure, and δ is a value less than 3), and an element Mb that substitutes for a part of Ma in the mother crystal to form a solid solution, The mother crystal is AMaO 3―δ The slope of the graph showing the relationship between the change in crystal lattice volume and the substitution solid solution ratio of Mb when Mb is dissolved in a perovskite crystal represented by the formula (1) is ∇a, AMaO in which δ of the perovskite crystal is filled with oxygen atoms 3 When the slope of a graph showing the relationship between the change in crystal lattice volume when Mb is dissolved in a solid solution and the substitution solid solution ratio of Mb is taken as ∇b, A solid electrolyte that is a crystal having a value of |∇a| / |∇b| that is greater than 0 and less than 1.
568.
2. The ionic radius of A is r A The weighted average value based on the abundance ratio of the elements of the ionic radii of Ma and Mb is r M Then, (r M / r A ) + C is 0.24 to 0.54, and C is C = 0.55 × r A The solid electrolyte according to claim 1, wherein the solid electrolyte has a viscosity of -0.
89.
3. The crystal lattice volume is 70.678 x 10 -3 nm 3 Above 85.052 x 10 -3 nm 3 3. The solid electrolyte according to claim 1 or 2, wherein:
4. Proton conductivity is 1.0×10 -3 S.C.M. -1 The solid electrolyte according to claim 1 or 2.
5. A is at least one selected from the group consisting of Ba, Sr, Ca, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Li, Na, K, Rb, Cs, and Mg; Each of the Ma and the Mb is at least one selected from the group consisting of Ti, Zr, Hf, Sn, Pb, Bi, Si, Ge, Ga, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Y, Lu, In, Sc, V, Nb, Ta, Cr, Mo, W, Sb, Mg, Al, As, and Re. The solid electrolyte according to claim 1 or 2.
6. General formula: BaSn 1-y S.C. y O 3-δ (y is a value of 0.2 to 0.7, and δ is a value of 0.2 to 3), general formula: BaTi 1-y S.C. y O 3-δ (wherein y is a value between 0.2 and 0.8, and δ is a value between 0 and 3), or a compound represented by the general formula: BaTi 1-y-x Sn y S.C. x O 3-δ (wherein y is a value of 0.05 to 0.15, x is a value of 0.2 to 0.8, and δ is a value of 0 to 3).
7. a first electrode; an electrolyte membrane provided on the first electrode; and a second electrode provided on a side of the electrolyte membrane opposite to the first electrode; A laminate, wherein the electrolyte membrane comprises the solid electrolyte according to claim 1 .
8. A fuel cell comprising the laminate according to claim 7.
Citation Information
Patent Citations
Solid electrolyte laminate, production method therefor and fuel cell
JP2013206703A